(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article presents the results of research of technological wells and gives recommendations to reduce the negative impact of complications on the efficiency of in-situ leaching technology. Development and implementation of effective technology of in-situ leaching of ores in conditions of complications is considered as a system of tasks.